Foreign Trade Pattern of Nepal: Gravity Model Approach - Prasai, Laxmi Prasad (NRB Economic Review, 2014)
This study examines the overall trade pattern and flow of trade of Nepal by using pooled ordinary least square (OLS) along with one-year lag gross domestic product (GDP). It has also attempted to find the structural shift in the economy after economic liberalization in Nepal. In this study, gravity model is applied with comprehensive panel dataset for 29 years time period covering Nepal’s 94 trading partners. The results appear robust to specification, time period and trade determinants. Following a convention in this field, this study separates exports and imports instead of using total trade turnover. The empirical results are found consistent with the fundamental of gravity model as the study reveals positive coefficients for economic size and negative coefficients for distance. No significant structural break is found in the determinants of trade after economic liberalization. The results from simulation while comparing actual trade with predicted trade show that Nepal’s trade is not distorted by political decisions such as economical sanctions imposed by other countries. The results also suggest that trade with India in comparison to China is quite substantial. The results suggest that Nepal needs trade diversification in general and trade agreement with China in particular to reap the benefits from the trade.